2017
DOI: 10.1108/jeas-02-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of banks liquidity: evidence from OIC countries

Abstract: Purpose Specifically, the purpose of this paper is to identify the key factors affecting banks’ liquidity in developing/less-developing countries. Design/methodology/approach In this paper, the author uses the ordinary least-square fixed effect model on an unbalanced panel data set of all conventional banks (686 banks) operating in the organization of Islamic cooperation countries over the period 1989-2008. Findings The estimation results show that all the determinants have statistically significant relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
4
11
0
2
Order By: Relevance
“…The regression results found that monetary policy interest rate has a negative impact with a coefficient of -.004 on the bank liquidity. This result is symmetrical with standard inferences in the literature due to the stringent effect of monetary policy on the bank (Vodová, 2013), (S. S. Bhati & De Zoysa, 2012), (Al-Harbi, 2017, (Laurine, 2013), (Valla et al, 2006), (Chen et al, 2014), (Malik & Rafique, 2013). However, the study found an insignificant impact on liquidity.…”
Section: Discussionsupporting
confidence: 86%
“…The regression results found that monetary policy interest rate has a negative impact with a coefficient of -.004 on the bank liquidity. This result is symmetrical with standard inferences in the literature due to the stringent effect of monetary policy on the bank (Vodová, 2013), (S. S. Bhati & De Zoysa, 2012), (Al-Harbi, 2017, (Laurine, 2013), (Valla et al, 2006), (Chen et al, 2014), (Malik & Rafique, 2013). However, the study found an insignificant impact on liquidity.…”
Section: Discussionsupporting
confidence: 86%
“…The significant difference in terms of the liquidity risk management between conventional banks and Islamic banks is visible in cash availability more in CBs than IBs. Al-Harbi (2017) investigates bank liquidity determinants of OIC countries. The research findings reveal that all the study’s explanatory variables maintain a significant association with liquidity, except for concentration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some indicators revealed negative relationship towards liquidity risk such as financing, capital adequacy ratio and inflation rate (Mohamad et al, 2013). A negative relationship between CAR and inflation also can be found in Al-Harbi (2017). While some studies found that capital adequacy ratio indicated a significant positive relationship towards liquidity risk (Ghenimi & Omri, 2015;Effendi & Disman, 2017;Linh et al, 2018).…”
Section: Past Studies Of Liquidity Riskmentioning
confidence: 94%
“…Also, the studies focus more on the important factors affecting liquidity risk which led to the scantiness of studies on the issue of bank liquidity which link to the capital structure. For instance, studies by Akhtar et al (2011); Iqbal (2012); Ramzan & Zafar (2012); Ahmed et al (2011); Amin et al (2017); Al-Harbi (2017) provided and empirical benchmarks for considering the major factors or determinants of bank liquidity risk. They found that liquidity risk is positively correlated with bank profitability, bank size, financial leverage and capital adequacy.…”
Section: Introductionmentioning
confidence: 99%